Investigation of the Acceleration Spectrum of a Vibratory Roller in the Process of Soil Compaction - Evgenij A. Shishkin; Alexander A. Smolyakov (Вестник СибАДИ)
Introduction. Successful quality control plays a crucial role in pavement compaction work. The main tool for continuous compaction monitoring is the frequency analysis of the vibratory acceleration spectrum of the roller. There are several indicators that are determined by the different harmonics of the acceleration frequency spectrum use. However, these indicators have a number of disadvantages, among which are low accuracy and limited scope of application. The aim of the study is to develop a universal compaction indicator that eliminates these disadvantages.Materials and methods. A single-mass oscillatory model describing the interaction of the system “vibratory roller – soil” has been created in Simulink environment. The model allows changing the soil parameters, such as stiffness and viscosity, as well as the operating parameters of the vibratory roller – amplitude and frequency of vibration. Fast Fourier transformation was used to study the frequency spectrum of roller acceleration.Results. As a result of modeling, frequency spectra of acceleration of the vibrating roller for different modes of roller operation were obtained. Through the analysis of the obtained data, a new indicator of compaction degree was proposed.Conclusion. On the basis of the proposed indicator the technique of determining the moment of time change from the periodic loss of contact (the partial uplift mode) to “double jump” mode is developed. Implementation of the methodology in operating performance will improve the efficiency of the process of soil compaction by a vibratory roller.